Sagot :
Answer:
x=11
Step-by-step explanation:
Variable x cannot be equal to any of the values -1,3 since division by zero is not defined. Multiply both sides of the equation by \left(x-3\right)\left(x+1\right), the least common multiple of x+1,x-3.
\left(x-3\right)\times 3=\left(x+1\right)\times 2
Use the distributive property to multiply x-3 by 3.
3x-9=\left(x+1\right)\times 2
Use the distributive property to multiply x+1 by 2.
3x-9=2x+2
Subtract 2x from both sides.
3x-9-2x=2
Combine 3x and -2x to get x.
x-9=2
Add 9 to both sides.
x=2+9
Add 2 and 9 to get 11.
x=11